Urgensi Perubahan Mindset Masyarakat Tentang Pentingnya Pendidikan Islam pada Generasi Muda di Desa Kolam - Robi Winata; Elfira Ariska; Nela Reza Putri Sagala; Ilham Ramadhan; Firsta Nada (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
The preparation of this article is based on our concern for education in Indonesia, which is still far from quality, especially for people in remote areas. It is very unfortunate with this problem. In the midst of the era of globalization and modernization, the more sophisticated technology is, there are still many people who do not appreciate the importance of education. There are several objective problems that make people tend not to attach importance to education. One of them is ignorance of the importance of education for survival. Many of the rural communities think narrowly about formal or non-formal or Islamic education, even though education plays an important role in supporting their lives in the future. Skills in critical thinking, collaboration and sharpening literacy skills are expected to be able to realize the younger generation of learners.